Supplementary report of the British Bering Sea Commissioners, January 31, 1893 [electronic resource]. - Dawson, George M., 1849-1901.; Baden-Powell, George, 1847-1898.; Great Britain. Bering Sea Commissioners. ([London? : s.n., 1893)
Tables. Signed: George Baden-Powell, George M. Dawson. At head of title: Behring Sea Arbitration. Includes bibliographical references. Electronic reproduction. Mode of access: Internet. 44